The Relationship Between Teachers’ ICT Abilities and Parental Guidance on Student Learning Motivation During The Covid-19 Pandemic in Batupapan - Perawati Patiung; Marwati Abdul Malik; Jaka Warsihna (Edumaspul: Jurnal Pendidikan, 2022)
The purpose of this study was to determine whether there is a relationship between the teacher's ICT ability and parental tutoring on students' learning motivation at SDN Gugus Batupapan, Tana Toraja Regency. This research was conducted on teachers of highgrade students, namely grades 4.5 and 6 at SDN Gugus Batupapan. The population of high-class students at SDN Gugus Batupapan is 587 students. In this study, the Yamane or Slovin formula was used to determine the sample size for students, namely by using probability sampling technique with random sampling so that a total sample of 247 students was obtained. While the population of the number of teachers as many as 24 teachers. The method used in this study to see the causal relationship of an independent variable (X) to a certain variable (Y) is to use the ex-post facto research method with the type of correlation research. This study used two types of analysis, namely descriptive statistical analysis and inferential statistical analysis on SPSS 24. Based on the statistical analysis of the teacher's ICT ability variable, the highest score was 105.00 and the lowest score was 74.00. The results of the analysis show that the mean is 88.3333, the median is 89.000, the mode is 89.00 and the standard deviation is 8.41152. Analysis of the variable data on parenting tutoring data obtained the highest score of 108.00 and the lowest score of 55.00. The results of the analysis show that the Mean is 83.8509, the Median is 83.00, the Mode is 75.00 and the Standard Deviation is 10.14893. Data analysis of students' learning motivation variables obtained the highest score of 111.00 and the lowest score of 55.00. The results of the analysis showed the Mean of 83.8138, the Median of 84,000, the Mode of 85.00 and the Standard Deviation of 11.96938. So it can be said that students' learning motivation is related to the ability of the teacher's ICT in terms of its application in the learning process. Parental tutoring is significantly related to the level of student learning motivation. Furthermore, the second variable, namely the ability of teachers' ICT and parental tutoring has a joint relationship with students' learning motivation.